Exploring the behavior of Candida antarctica lipase B in aqueous mixtures of an imidazolium ionic liquid and its surfactant analogue - Campodónico, Paola R.; Calderón, Cristian; Alcázar, Jackson J.; Olivares, Belén; Jaldin, Limberg; Suárez-Rozas, Cristian (Frontiers in Chemistry, 2024)
Candida antarctica lipase B (CALB) performance has been evaluated in 1-butyl-3-methylimidazolium tetrafluoroborate (BMIMBF4)/water mixtures in a wide range of molar fractions ( 𝐵𝑀𝐼𝑀𝐵𝐹4 ) with and without 1-dodecyl-3-methylimidazolium tetrafluoroborate (C12-MIMBF4), a surfactant derived from BMIMBF4. The main aim of this work is to evaluate the influence of  𝐵𝑀𝐼𝑀𝐵𝐹4 over micellar aggregates to assess the activity of enzymatic reactions. The investigated reaction corresponds to the hydrolysis of the substrate p-nitrophenyl laureate (p-NPL) in each  𝐵𝑀𝐼𝑀𝐵𝐹4 . The kinetic study for  𝐵𝑀𝐼𝑀𝐵𝐹4 around 0.2 proved to be a border point in enzymatic activity. At  𝐵𝑀𝐼𝑀𝐵𝐹4 = 0.1, the lipase activity increases in the presence of C12-MIMBF4. However, at higher concentrations, BMIMBF4 has a negligible effect over the lipase activity. These results suggest specific interactions between water and BMIMBF4 molecules in relation to CALB. This research highlights the superactivity phenomenon driven by the reaction media and the micelle interface. In this interfacial interaction, BMIMBF4 acts directly on the changes induced on the enzyme upon its interaction with the micellar interface. This study opens a green perspective towards the biocatalysis field.